COMPLIENCE (KEPATUHAN) IBU DALAM MEMBERIKAN OBAT PADA ANAK DENGAN PENYAKIT INFEKSI SALURAN PERNAFASAN AKUT (ISPA) - Amran, Husna Farianti; Kirana, Desi Nindya (Universitas Malahayati Bandar Lampung, 2022)
Introduction: Acute respiratory infection (ARI) is an infection that affects the structure of the respiratory tract above the larynx, but most of these diseases affect the upper and lower tract simultaneously or sequentially (Nelson, 2000). In general, the causes of respiratory tract infections are various microorganisms, but most are due to viral and bacterial infections. Factors that influence the spread of respiratory tract infections include environmental factors such as smoke outbreaks, poor public behavior towards personal and public health, and low nutrition.The Purpose The purpose of this study was to determine the factors that influence maternal compliance in giving drugs to children with Acute respiratory infection (ARI)Methods: This type of research is quantitative with an analytic design with a coss sectional approach. The population of all mothers who have children who experience ARI at BPM Islah Wahyuni Pekanbaru April-May 2022 as many as 189 people. Data were collected using a questionnaire and analyzed univariate and bivariate using the chi-square test (X2).Results: Variables that have statistical significance affect maternal compliance in giving drugs to children with ARI, namely knowledge about disease (P value 0.025), anxiety about drug side effects (P value 0.029), support from health workers (P value 0.018)Conclusion: Mother's compliance in giving medication to children with ARI (Upper Respiratory Tract Infection) is influenced by: Mother's knowledge about the disease, anxiety about drug side effects, and support from health workers. For this reason, it is suggested that midwives should provide support in the form of health education in order to increase maternal knowledge about ARI and reduce maternal anxiety about the side effects of ARI drugsSuggestion Midwives should provide support in the form of health education in order to increase maternal knowledge about ARI and reduce maternal anxiety about the side effects of ARI drugs. This is because the support from health workers is related to the compliance of mothers in giving drugs to children. Keywords : chronic toxoplasmosis infection, cat hygiene, cage sanitation